The Conceptual Study Regarding ABC System Implementation: Evidence from Jordanian Companies. (Global Business Management Review (GBMR), 2022)
This paper attempts to contribute to the design and the successful ABC implementation in the Jordanian manufacturing companies. The research methodology included both quantitative and qualitative techniques. The questionnaire survey was developed for the primary aims of determining the current state of, and the factors which influence ABC adoption and implementation. In the second stage, semi-structured interviews will be conducted with 13 companies for more probe and clarification. The analysis of the data will be run by using both ‘within company’ and ‘cross-company’ analysis. The results will determine the three criteria that are used to determine the adoption and implementation rate of ABC and the factors which influence ABC adoption and implementation.